Defesa e controle: uma análise da presença civil no ministério da defesa brasileiro - Pimenta, Gabriel Alves (2014)
This thesis aims to examine the contribution of civilian presence towards the establishment of civil control over the military under civilian perspective in the Ministry of Defense. Using a qualitative approach this research aimed to present a new point of view of civil participation in the administration of the Defense folder, usually addressed through military perception. Interviews were conducted with 11 civil servants working in the Ministry in order to capture their perception on civilian participation on their field of operation. Highlighting the strong military culture present in the field, the interaction between civilian and military and the qualification and training of civilians working in the field. Evidence collected focused on the control suggest that, in contrast to the official discourse and despite the advances made in recent years, civilian control of the process still needs to progress and reach key elements in order to be deemed to be established.